การแยกขยะชุมชนย่อยขนาดในฟลูอิไดซ์เบดแบบสามวัฏภาค - ดนย์วิทย์ ประทีปวัฒนาสถิต (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
This research studied separation of shredded municipal waste containing papers, plastics and organic waste for biogas production. In experiment, Three phase fluidized bed reactor was used in session. In this process, water and air contributed plastic and paper to top of column and high density organic waste was lead to bottom of column. The research was divided into two steps. First to study and test separation performance of Three phases fluidized bed reactor. The variables were water flow rate, air flow rate and feed flow rate. The result shown that separate performance PC plastic (polycarbonate) from PA plastic (polyamide) in reactor was 0.67.Subsequently, the method and experimental was tested in real waste. The water flow rates in this study were 20, 25, 30, 35 and 40 L/min. Air flow rates were 0, 10, 15 and 20 L/hr. Feed flow rates were 60, 85, 100 and 200 g/min. Furthermore, sizes of plastic waste which were 1x3 and 1x5 cm2 were studied. The result shown that size of plastic has no significant in separate performance and optimum performance was 0.87. The appropriate factors were 35 L/min of water flow rate, 20 L/hr. of air flow rate and 85 g/min of feed flow rate.